Axiology of Transbaikal Territory Media Image - Irina V. Erofeeva; Natalya V. Prostakishina (Гуманитарный вектор)
Region’s media image modelling is a very topical problem of the information age from the view of productive functioning of territories, their socio-economic and political status. The article presents the role of values in the media image structure, analyzes axiological components of the Transbaikal Territory media image, and shows its cultural and content characteristics. Research findings are based on some data from a sociological survey carried out in 2021, where 911 residents of the region of different ages (20 to 68) took part, as well as the results of a survey of 48 regional journalists from different communication channels. The attention is paid to the conceptual component of the Region Media Image, as well as to the special role of the actor of multimedia content. Typological and cognitive analyses allowed us to identify the empirical material and present it as a system of cultural and historical dominant ideas. Major characteristics of media image axiology are based on linguocultural approach, emphasizing the values of traditional culture. Media image axiology presents a triple-stage system with its regional specific features, distinct content including spiritual and moral, cultural and historical, and natural values. Spiritual and moral priorities reflect region’s mental view of the world and focus on the values of labour, kindness, grace, sincerity and patriotism, preservation of family values, faith in justice. Cultural and historical context is enriched by the folk heroes of the past and present, traditions, beliefs and customs. Coronavirus pandemic made actors of information flows focus on natural resources of Transbaikalia. During the study, we revealed a correlation between the axiological instrumentation of designing the media image of the region and the level of influence of the media discourse on the consumer, between the spiritual and moral picture of the author’s view of the world and the demand for media products by the audience. We justify the need to adjust the work of regional journalists with a texture inherent in modelling the media image of the region.The authors make a conclusion that, on the one hand, a productive media image is designed using values and ideals characteristic of the territory, on the other hand, the cultural and historical space of the region is a tool for necessary identification with a place of residence, a link between generations and residents of the region.